2013
DOI: 10.1097/ana.0b013e318290c230
|View full text |Cite
|
Sign up to set email alerts
|

Awake Craniotomy for Brain Tumor Resection

Abstract: Given the effectiveness of AC for resection of eloquent tumors, the data suggests an expanded role for AC in brain tumor surgery regardless of tumor location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 0 publications
0
43
1
5
Order By: Relevance
“…remifentanil). A recent systematic review showed that awake brain tumor resection led to a better perioperative neurological outcome compared with surgery under general anesthesia; moreover, AC was consistently associated with shorter hospital stay, less resource utilization, and high patient satisfaction 13 . Major intraoperative complications during AC include respiratory depression, arterial hypertension, nausea and vomiting, air embolisms, brain swelling, seizures and loss of patient cooperation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…remifentanil). A recent systematic review showed that awake brain tumor resection led to a better perioperative neurological outcome compared with surgery under general anesthesia; moreover, AC was consistently associated with shorter hospital stay, less resource utilization, and high patient satisfaction 13 . Major intraoperative complications during AC include respiratory depression, arterial hypertension, nausea and vomiting, air embolisms, brain swelling, seizures and loss of patient cooperation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, factors that increase LOS include preoperative comorbidities, prolonged operative time, fluid volume infused intraoperatively, intraoperative blood loss, and time to tolerate oral fluids postoperatively . Moreover, the surgical procedure itself has been shown to impact LOS as patients undergoing awake craniotomies have a shorter LOS than those treated with craniotomies under general anesthesia …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Moreover, the surgical procedure itself has been shown to impact LOS as patients undergoing awake craniotomies have a shorter LOS than those treated with craniotomies under general anesthesia. 7 In contrast to adult brain tumor patients, there is a paucity of literature on factors that influence LOS in pediatric neuro-oncology. The limited available data on LOS in pediatric brain tumor patients have identified postoperative wound infections, 8 posterior fossa tumor resection, 8,9 intraoperative blood loss, and difficult extubation 10 to prolong LOS.…”
mentioning
confidence: 99%
“…Studies have demonstrated that up to 50% of patients with acute subarachnoid hemorrhage (SAH) suffer from some degree of neurological impairment after aneurysm clipping [1,2]. In patients with acute stroke who have a high rate of neurological morbidity, therapies that provide neuroprotection are the mainstay of clinical management [3,4].…”
Section: Introductionmentioning
confidence: 99%